2018
DOI: 10.3389/fpls.2018.01827
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Alleles of Heading date 1 (Hd1) Are Associated With Adaptation of Temperate Japonica Rice Plants to the Tropical Region

Abstract: Adaptation of temperate japonica rice varieties to tropical regions is impeded by extremely early flowering probably due to photoperiod change from long to short. However, constant breeding efforts led to development of temperate japonica varieties adapted to tropical/subtropical regions, but the genetic factor underlying this is still elusive. We analyzed the 45 diverse rice accessions and 12 tropical-adapted temperate japonica lines for the allele types of seven major flowering genes Hd1, OsPPR37, DTH8, Ghd7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Thus, the authors suggested that Hd1 was a possible target of selection to generate different flowering-time responses in different regions. Kim et al [ 60 ] selected about 60 diverse rice accessions to analyze the Hd trait of various types, including 4 aus accessions, 20 indica accessions, 4 tropical japonica accessions, 17 temperate japonica accessions, and 12 tropical adapted temperate japonica accessions. The authors analyzed 7 major flowering genes, including Hd1 [ 9 ], OsPPR37 [ 61 ], DTH8 [ 62 ], Ghd7 [ 12 ], Ehd1 [ 10 ], RFT1 [ 63 ] and Hd3a [ 11 ] as well as heading behavior under 3 different field conditions in temperate and tropical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the authors suggested that Hd1 was a possible target of selection to generate different flowering-time responses in different regions. Kim et al [ 60 ] selected about 60 diverse rice accessions to analyze the Hd trait of various types, including 4 aus accessions, 20 indica accessions, 4 tropical japonica accessions, 17 temperate japonica accessions, and 12 tropical adapted temperate japonica accessions. The authors analyzed 7 major flowering genes, including Hd1 [ 9 ], OsPPR37 [ 61 ], DTH8 [ 62 ], Ghd7 [ 12 ], Ehd1 [ 10 ], RFT1 [ 63 ] and Hd3a [ 11 ] as well as heading behavior under 3 different field conditions in temperate and tropical regions.…”
Section: Discussionmentioning
confidence: 99%
“…They included cultivars grown in Spain (Guara, J. Sendra, Puntal, Gleva, and Bomba), Italy (Loto, Gigante Vercelli, Maratelli, Galileo, and Selenio) and France (Gines) (Courtois et al 2012;Reig-Valiente et al 2016). A Taiwanese cultivar Tainung 67 (TN67) closely related to Japanese and Korean temperate japonica varieties (Kim et al 2018) was also included in this panel. Rice plants were grown in the greenhouse under controlled conditions (14 h/10 h day/night cycle, 28°C/25°C, and 60% humidity).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The tenth exon of Hd16 was amplified by polymerase chain reaction (PCR) using the primers and conditions described in Supplementary Table S1 . The two exons of Hd1 and the two exons of Ghd7 were amplified by PCR as described in [ 22 ]. Sequencing of the PCR products was performed by Macrogen (Daejeon, Korea).…”
Section: Methodsmentioning
confidence: 99%